The effect of variable troponin C mutation thin filament incorporation on cardiac muscle twitch contractions. (June 2021) - Mijailovich, Srboljub M.; Prodanovic, Momcilo; Poggesi, Corrado; Powers, Joseph D.; Davis, Jennifer; Geeves, Michael A.; Regnier, Michael
Abstract: One of the complexities of understanding the pathology of familial forms of cardiac diseases is the level of mutation incorporation in sarcomeres. Computational models of the sarcomere that are spatially explicit offer an approach to study aspects of mutational incorporation into myofilaments that are more challenging to get at experimentally. We studied two well characterized mutations of cardiac TnC, L48Q and I61Q, that decrease or increase the release rate of Ca 2+ from cTnC, k − Ca, resulting in HCM and DCM respectively [1 ]. Expression of these mutations in transgenic mice was used to provide experimental data for incorporation of 30 and 50% (respectively) into sarcomeres. Here we demonstrate that fixed length twitch contractions of trabeculae from mice containing mutant differ from WT; L48Q trabeculae have slower relaxation while I61Q trabeculae have markedly reduced peak tension. Using our multiscale modelling approach [2 ] we were able to describe the tension transients of WT mouse myocardium. Tension transients for the mutant cTnCs were simulated with changes in k − Ca, measured experimentally for each cTnC mutant in whole troponin complex, a change in the affinity of cTnC for cTnI, and a reduction in the number of detached crossbridges available for binding. A major advantage of the multiscale explicit 3-D model is that it predicts the effects of variable mutation incorporation, and the effects of variations in mutation distribution within thin filaments in sarcomeres. Such effects are currently impossible to explore experimentally. We explored random and clustered distributions of mutant cTnCs in thin filaments, as well as distributions of individual thin filaments with only WT or mutant cTnCs present. The effects of variable amounts of incorporation and non-random distribution of mutant cTnCs are more marked for I61Q than L48Q cTnC. We conclude that this approach can be effective for study on mutations in multiple proteins of the sarcomere. Summary: A challenge in experimental studies of diseases is accounting for the effect of variable mutation incorporation into myofilaments. Here we use a spatially explicit computational approach, informed by experimental data from transgenic mice expressing one of two mutations in cardiac Troponin C that increase or decrease calcium sensitivity. We demonstrate that the model can accurately describe twitch contractions for the data and go on to explore the effect of variable mutant incorporation and localization on simulated cardiac muscle twitches. Graphical abstract: Unlabelled Image Highlights: Familial cardiac diseases usually originate from mutations in sarcomeric proteins. The L48Q and I61Q mutations in cTnC modulate the release rate of Ca 2+ from cTnC. The effects of the cTnC mutations are evaluated by in silico simulations. Twitch contractions in L48Q trabeculae have slower relaxation than WT while in I61Q trabeculae have lower peak tension than WT. An explicit 3-D model predicts the effects of variable incorporation of mutations.